Challenges and new horizons in the periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome. (1st February 2017) - Gentileschi, Stefano; Vitale, Antonio; Frediani, Bruno; Galeazzi, Mauro; Rigante, Donato; Cantarini, Luca
ABSTRACT: Introduction: Periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome is a multifactorial autoinflammatory disorder representing a true challenge for differential diagnosis of fevers of unknown origin among children. Areas covered: Although current diagnostic criteria confine PFAPA syndrome into the pediatric world, recent evidences have suggested the possible onset of this disease during adulthood as well as the possible relapse over time after spontaneous or treatment-induced resolution in childhood. The number of treatment choices currently available is growing significantly. In this regard, inhibition of interleukin (IL)-1 represents an intriguing promise for PFAPA patients who do not respond to standard therapy or for whom corticosteroid administration is unsuitable. Expert opinion: The challenges associated with the discovery of pathogenetic pathways and treatment alternatives in PFAPA syndrome are immense, reflected by the small number of studies currently in progress. As new mechanisms underlying the regulation of innate immunity are discovered and novel therapeutic approaches are adopted, the next decade promises many exciting advances to manage and treat patients with PFAPA syndrome.